2010
DOI: 10.1049/el.2010.3246
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric ferrite sheets for SAR reduction of wearable antennas

Abstract: Reduction of specific absorption rate (SAR) has now become a buzz word because of the growing health concerns over microwave exposure. Ferrites are found to be effective in diminishing electromagnetic influence. In this reported work, flexible polymeric ferrite sheets are characterised on the basis of their shielding efficiencies. SAR measurements are carried out with a planar wearable antenna and polymeric ferrite shielding to confirm its competence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Foreseeing this limitation, researchers have extensively evaluated various facets of the on-body degradation [7][8][9][10]. Examinations of bending effects [7], worn efficiency [8], and material changes due to environmental conditions [9], in addition to the various suggested methods to limit the influence of body coupling-absorption, have been presented [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foreseeing this limitation, researchers have extensively evaluated various facets of the on-body degradation [7][8][9][10]. Examinations of bending effects [7], worn efficiency [8], and material changes due to environmental conditions [9], in addition to the various suggested methods to limit the influence of body coupling-absorption, have been presented [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous SAR literature mostly reported antennas and communication devices made from conventional printed circuit boards operating near the human head or hands [12][13][14][15][16]. Other researchers have suggested several SAR reduction techniques, e.g., by implementing ferrites [11], electromagnetic bandgap structures [17,18], and resistive sheets [19]. Meanwhile, several recent reports have evaluated antenna SARs radiating inward/toward parts of the human body.…”
Section: Introductionmentioning
confidence: 99%
“…In [6], a ferrite sheet was adopted as a protection attachment between the antenna and the human head. In [7], a study on the belongings of attaching conductive materials to the cellular phone for SAR reduction has been offered.…”
Section: Introductionmentioning
confidence: 99%
“…From a lot of practical and empirical experience we had, the body SAR in 5‐GHz WLAN band is usually higher than that in the 2.4 GHz band from the antenna given by the same input power. A few research studies on the SAR reduction have been reported in the literature , in which two main types of methods were mainly used. First, it has been shown that the SAR can be reduced by placing the ferrite sheet between the antenna and the torso or the metamaterials between the antenna and the head .…”
Section: Introductionmentioning
confidence: 99%